National Health Interview Survey, 1991: Child Health Supplement ([Verlag nicht ermittelbar], 1993)
The purpose of the National Health Interview Survey (NHIS) is to obtain information about the amount and distribution of illness, its effects in terms of disability and chronic impairments, and the kinds of health services people receive. The 1991 Child Health Supplement provides variables from the core Person File (see NATIONAL HEALTH INTERVIEW SURVEY, 1991 [ICPSR 6049]) including sex, age, race, marital status, veteran status, education, income, industry and occupation codes, and limits on activity. Variables unique to this supplement cover childhood immunizations and whether children were vaccinated for diphtheria, tetanus, pertussis, polio, measles, mumps, and rubella. Additionally, questions were asked about occurrences of diarrhea and ear infections, other possible physical and mental conditions, and whether the children were in day care with other children. Questions about seat belt usage and organized sports participation were asked as well.